Non-carbonization process formed coke binder and formed coke and preparation method thereof

By using components such as tar asphalt, phenolic resin, clay, water glass and ceramic fiber in the pyrox binder, the problems of decreasing strength and poor compatibility of pyrox binder in high temperature environments are solved, and the high temperature stability and structural uniformity of pyrox are achieved.

CN119875708APending Publication Date: 2025-04-25SHENZHEN ZHUYOU MECHANICAL & ELECTRICAL EQUIPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510130192.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The strength of the existing coke binders decreases in high temperature environments and are poorly compatible with coal particles, resulting in uneven internal structure of the coke and affecting performance stability.

Method used

Tar asphalt is used as the base bonding component and combined with phenolic resin to form a three-dimensional mesh system. The compatibility is improved through clay, the water glass is accelerated to form and water resistance, and the ceramic fiber reinforces structural stability.

Benefits of technology

It improves the high-temperature stability and compatibility of the coke, ensures the stable shape after molding, enhances the bonding strength and wear resistance, and reduces the negative impact on the fixed carbon content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a non-carbonization process formed coke binder and formed coke and a preparation method thereof.The formed coke binder comprises ceramic fibers, tar pitch, phenolic resin, clay, water glass, a curing agent, a plasticizer, a waterproof agent and a filling material.By optimizing the formula of the formed coke binder, the negative influence on the fixed carbon content of the formed coke is effectively reduced, and the formed coke is more environmentally friendly. The performance of the formed coke can be optimized through raw material matching, the fixed carbon content, sulfur content, ash content and volatile components can be accurately adjusted, and reliable technical guarantee is provided for large-scale application and popularization of the non-carbonization process formed coke in the industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field

[0003] Based on their chemical composition, molded coke binders can be divided into inorganic binders (such as clay, water glass, cement, and phosphates) and organic binders (such as coal tar, asphalt, and synthetic resins). While inorganic binders offer relatively low cost and better environmental performance, they often suffer from insufficient bonding strength. This is particularly true in high-temperature environments, where the strength of the molded coke decreases significantly, making them unable to meet the high-quality demands of some industrial production processes. While organic binders offer superior bonding properties and can impart high initial strength to molded coke, they are generally expensive and release significant amounts of volatiles during the carbonization process. These volatiles, including organic pollutants such as benzene and naphthalene, can cause significant environmental pollution and affect the final quality of the molded coke, making it difficult to achieve ideal thermal stability and reactivity. Furthermore, both inorganic and organic binders suffer from poor compatibility with coal particles, resulting in a lack of uniform structure within the molded coke, further impacting the coke's performance stability. This, in turn, limits the large-scale application and promotion of non-carbonized process molded coke in industry. [Summary of the invention] The purpose of the present invention is to provide a non-carbonized process coke binder to solve the problem that the current single type of binder has poor compatibility with raw material particles, resulting in uneven internal structure and thus affecting its performance stability.

[0005] A non-carbonized process coke binder, characterized by comprising the following components in parts by weight: Ceramic fiber: 3-12 parts; Tar pitch: 5-15 parts; Phenolic resin: 3-10 parts; Clay: 10-20 parts; Water glass: 5-15 parts; Curing agent: 5-10 parts; Plasticizer: 1-5 parts; Waterproofing agent: 1-3 parts; Filling material: 10-20 parts.

[0006] The present invention uses tar pitch as the basic bonding component, and its good viscosity and fluidity provide basic bonding properties for the adhesive; by combining phenolic resin with tar pitch, cross-linking can occur during the molding of coke to form a three-dimensional network system, and a protective film can be formed on the surface and inside of the coke, effectively preventing the erosion of moisture and chemicals; clay is used to adjust the viscosity of the bonding system, improving the compatibility of the binder and the particles, so that the coke can maintain a stable shape after molding and is not easily deformed; water glass is used to quickly form a layer of highly viscous gel film on the surface of the particles, which can accelerate the molding of the coke and form a hard protective layer with good water resistance and weathering resistance after drying; finally, ceramic fibers are used to form a three-dimensional supporting network structure inside the coke, strengthening the skeleton of the bonding system, thereby dispersing stress and preventing the expansion of cracks. In addition, ceramic fibers have excellent stability in high temperature environments and can effectively prevent the collapse of the coke structure under high temperature conditions.

[0007] Preferably, the filling material may be one or more combinations of calcium carbonate, talc, and fly ash.

[0008] Another object of the present invention is to provide a method for preparing a non-carbonization process type coke binder.

[0009] The preparation method of the non-carbonization process type coke binder comprises the following steps: S1. Pretreatment: Processing the ceramic fiber into a specific size for standby use, and then heating the tar pitch to a specific temperature for standby use; S2, preliminary mixing: adding phenolic resin to the tar pitch described in step S1, stirring until the phenolic resin and the tar pitch are uniformly mixed to obtain a mixture; S3, secondary mixing: slowly adding clay to the mixture of step S2, stirring until the clay is completely wrapped in the mixture of step S2, adding plasticizer, waterproofing agent and curing agent in sequence, stirring, and then slowly adding water glass, stirring until the water glass and the mixture are evenly mixed; S4, tertiary mixing: adding the ceramic fiber described in step S1 to the mixture described in step S3, stirring until the ceramic fiber and the mixture are evenly mixed, then adding the filling material, stirring, and obtaining the molded coke binder.

[0010] The present invention first pre-processes the ceramic fibers into a specific size, allowing them to be evenly distributed within the binder, improving the binder's fluidity and reducing defects such as pores and cracks. The fibers also form an effective reinforcement network with the binder, increasing the binder's tensile strength, compressive strength, and durability. Tar pitch is heated to a suitable temperature and softened to allow for better uniform mixing with other components, such as phenolic resin. Secondly, a multi-stage mixing process, involving initial mixing, secondary mixing, and tertiary mixing, is employed, with a specific order of addition followed to gradually form a structurally stable bonding system.

[0011] Preferably, the stirring speed is 300-500 r / min, and the stirring time is 10-40 min.

[0012] Preferably, the processing method in step S1 is shearing or grinding.

[0013] Preferably, the specific temperature in step S1 is higher than the softening point of the tar pitch.

[0014] The present invention heats the tar pitch to a temperature higher than its softening point to make it in a suitable fluid state, and then uniformly mixes it with the phenolic resin in the preliminary mixing step to form a good bonding system and improve the overall bonding performance of the adhesive.

[0015] Another object of the present invention is to provide a molded coke comprising the non-carbonized process coke binder, wherein the non-carbonized process coke binder accounts for 10-20% of the total mass of the molded coke.

[0016] By ensuring the proper proportion of binder in the molded coke, this method ensures that particles such as coke powder, coke dust, and coke dices can be effectively bonded and formed when mixed with the binder. Furthermore, the binder for molded coke is free of magnesium, phosphorus, aluminum, iron, and other harmful chemical components, minimizing the negative impact on the fixed carbon content of the molded coke. This allows precise adjustment of the fixed carbon content, sulfur content, ash content, and volatile matter of the molded coke by adjusting the raw materials to meet the needs of different application scenarios.

[0017] The present invention proposes a non-carbonized process coke binder, which uses tar pitch as a basic binder. By combining tar pitch with phenolic resin, a three-dimensional bonding system can be formed during the coke molding process, thereby enhancing the bonding strength and high-temperature resistance. Clay is used to improve the compatibility between the binder and particles, so that the coke can maintain a stable shape after molding. Water glass is used to accelerate the molding of the coke, improve water resistance and weathering resistance, and finally, ceramic fibers are used to strengthen, toughen and stabilize the coke structure system, thereby improving high-temperature stability.

[0018] The present invention also proposes a method for preparing a non-carbonized process-type coke binder. Through pretreatment, ceramic fibers are processed into specific sizes, and tar pitch is heated to an appropriate temperature to ensure that they can be evenly distributed during the subsequent mixing process; a multi-stage mixing method of preliminary mixing, secondary mixing and tertiary mixing is adopted, and a structurally stable bonding system is gradually formed according to a specific addition order.

[0019] The present invention also proposes a molded coke comprising the non-carbonization process coke binder. The molded coke binder can effectively reduce the negative impact on the fixed carbon content, so that the fixed carbon content, sulfur content, ash content and volatile matter of the molded coke can be accurately adjusted through the combination of raw materials, providing reliable technical guarantee for the large-scale application and promotion of non-carbonization process coke in industry. [Specific implementation method] The specific technical solutions of the present invention are described below in conjunction with Examples 1-3: Example 1: The preparation method of the non-carbonization process type coke binder comprises the following steps: S1. Pretreatment: 6 parts of ceramic fibers are processed into a specific size and set aside, and 10 parts of tar pitch are heated to a specific temperature and set aside; S2, preliminary mixing: adding 5 parts of phenolic resin to the tar pitch described in step S1, stirring at 300 r / min for 10 minutes until the phenolic resin and the tar pitch are uniformly mixed to obtain a mixture; S3, secondary mixing: slowly adding 15 parts of clay to the mixture of step S2, stirring for 25 minutes until the clay is completely wrapped in the mixture of step S2, sequentially adding 3 parts of plasticizer, 2 parts of waterproofing agent and 7 parts of curing agent, stirring for 10 minutes, and then slowly adding 10 parts of water glass, stirring for 12 minutes, until the water glass and the mixture are evenly mixed; S4, tertiary mixing: adding the ceramic fiber described in step S1 to the mixture described in step S3, stirring for 30 minutes until the ceramic fiber and the mixture are evenly mixed, then adding 12 parts of the filling material, stirring for 10 minutes, to obtain a molded coke binder.

[0021] Example 2: The preparation method of the non-carbonization process type coke binder comprises the following steps: S1. Pretreatment: 9 parts of ceramic fibers are processed into a specific size and set aside, and 12 parts of tar pitch are heated to a specific temperature and set aside; S2, preliminary mixing: adding 7 parts of phenolic resin to the tar pitch described in step S1, stirring at 400 r / min for 15 minutes until the phenolic resin and the tar pitch are uniformly mixed to obtain a mixture; S3, secondary mixing: slowly adding 18 parts of clay to the mixture of step S2, stirring for 25 minutes until the clay is completely wrapped in the mixture of step S2, sequentially adding 4 parts of plasticizer, 3 parts of waterproofing agent and 8 parts of curing agent, stirring for 12 minutes, and then slowly adding 12 parts of water glass, stirring for 15 minutes, until the water glass and the mixture are evenly mixed; S4, tertiary mixing: adding the ceramic fiber described in step S1 to the mixture described in step S3, stirring for 35 minutes until the ceramic fiber and the mixture are evenly mixed, then adding 15 parts of filler material, stirring for 13 minutes, to obtain a molded coke binder.

[0022] Example 3: The preparation method of the non-carbonization process type coke binder comprises the following steps: S1. Pretreatment: 12 parts of ceramic fibers are processed into a specific size and set aside, and 15 parts of tar pitch are heated to a specific temperature and set aside; S2, preliminary mixing: adding 10 parts of phenolic resin to the tar pitch described in step S1, stirring at 450 r / min for 20 minutes until the phenolic resin and the tar pitch are uniformly mixed to obtain a mixture; S3, secondary mixing: slowly adding 20 parts of clay to the mixture of step S2, stirring for 28 minutes until the clay is completely wrapped in the mixture of step S2, sequentially adding 5 parts of plasticizer, 3 parts of waterproofing agent and 10 parts of curing agent, stirring for 10 minutes, and then slowly adding 15 parts of water glass, stirring for 15 minutes, until the water glass and the mixture are evenly mixed; S4, tertiary mixing: adding the ceramic fiber described in step S1 to the mixture described in step S3, stirring for 40 minutes until the ceramic fiber and the mixture are evenly mixed, then adding 10 parts of filler material, stirring for 15 minutes, to obtain a molded coke binder.

[0023] Comparative Example 1: The preparation method of the molded coke binder comprises the following steps: S1. Pretreatment: 15 parts of tar pitch are heated to a specific temperature and set aside; S2, preliminary mixing: adding 10 parts of phenolic resin to the tar pitch described in step S1, stirring at 450 r / min for 20 minutes until the phenolic resin and the tar pitch are uniformly mixed to obtain a mixture; S3, secondary mixing: slowly adding 20 parts of clay to the mixture of step S2, stirring for 28 minutes until the clay is completely wrapped in the mixture of step S2, sequentially adding 5 parts of plasticizer, 3 parts of waterproofing agent and 10 parts of curing agent, stirring for 10 minutes, and then slowly adding 15 parts of water glass, stirring for 15 minutes, until the water glass and the mixture are evenly mixed; S4, tertiary mixing: adding 10 parts of the filling material to the mixture in step S3, stirring for 15 minutes until the filling material and the mixture are evenly mixed to obtain a molded coke binder.

[0024] Comparative Example 2: The preparation method of the molded coke binder comprises the following steps: S1. Pretreatment: 12 parts of ceramic fibers are processed into specific sizes for standby use; S2. Preliminary mixing: slowly add 20 parts of clay to 10 parts of phenolic resin, and stir at 450 r / min for 28 minutes until the phenolic resin and the clay are evenly mixed to obtain a mixture; S3, secondary mixing: sequentially adding 5 parts of plasticizer, 3 parts of waterproofing agent and 10 parts of curing agent to the mixture of step S2, stirring for 10 minutes, and then slowly adding 15 parts of water glass, stirring for 15 minutes, until the water glass and the mixture are evenly mixed; S4, tertiary mixing: adding the ceramic fiber described in step S1 to the mixture described in step S3, stirring for 40 minutes until the ceramic fiber and the mixture are evenly mixed, then adding 10 parts of filler material, stirring for 15 minutes, to obtain a molded coke binder.

[0025] Comparative Example 3: The preparation method of the molded coke binder comprises the following steps: S1. Pretreatment: 12 parts of ceramic fibers are processed into a specific size and set aside, and 15 parts of tar pitch are heated to a specific temperature and set aside; S2. Preliminary mixing: slowly add 20 parts of clay to the tar pitch described in step S1, and stir at 450 rpm for 28 minutes until the clay and the tar pitch are evenly mixed to obtain a mixture; S3, secondary mixing: sequentially adding 5 parts of plasticizer and 3 parts of waterproofing agent to the mixture of step S2, stirring for 10 minutes, and then slowly adding 15 parts of water glass, stirring for 15 minutes, until the water glass and the mixture are evenly mixed; S4, tertiary mixing: adding the ceramic fiber described in step S1 to the mixture described in step S3, stirring for 40 minutes until the ceramic fiber and the mixture are evenly mixed, then adding 10 parts of filler material, stirring for 15 minutes, to obtain a molded coke binder.

[0026] Comparative Example 4: The preparation method of the molded coke binder comprises the following steps: S1. Pretreatment: 12 parts of ceramic fibers are processed into a specific size and set aside, and 15 parts of tar pitch are heated to a specific temperature and set aside; S2, preliminary mixing: adding 10 parts of phenolic resin to the tar pitch described in step S1, stirring at 450 r / min for 20 minutes until the phenolic resin and the tar pitch are uniformly mixed to obtain a mixture; S3, secondary mixing: add 5 parts of plasticizer, 3 parts of waterproofing agent and 10 parts of curing agent to the mixture in step S2 in sequence, and stir for 10 minutes until the mixture is evenly mixed; S4, tertiary mixing: adding the ceramic fiber described in step S1 to the mixture described in step S3, stirring for 40 minutes until the ceramic fiber and the mixture are evenly mixed, then adding 10 parts of filler material, stirring for 15 minutes, to obtain a molded coke binder.

[0027] Table 1 Components of Examples 1-3 and Comparative Examples 1-3

[0028] The molded coke binders of Examples 1-3 and Comparative Examples 1-3 were respectively used to bond coke dust and coke ash together, and molded coke was obtained by cold pressing and solidification. The performance of the molded coke was tested according to the test standard "GB / T 1996-2017 Metallurgical Coke".

[0029] Table 2 Test data of cokes in Examples 1-3 and Comparative Examples 1-3

[0030] As can be seen from Table 2, compared with Comparative Examples 1-4, the shaped coke obtained in Examples 1-3 has a higher fixed carbon content, lower ash, sulfur, volatile matter and coke fines content, and has excellent mechanical strength and wear resistance.

[0031] Compared to Example 3 and Comparative Examples 2-3, the fixed carbon content, ash content, sulfur content, volatile matter, coke content, mechanical strength, and wear resistance of Comparative Example 1, which lacked ceramic fiber, were significantly reduced. Furthermore, compared to Example 3, the fixed carbon content, ash content, sulfur content, volatile matter, coke content, mechanical strength, and wear resistance of Comparative Example 2, which lacked tar pitch, Comparative Example 3, which lacked phenolic resin and curing agent, and Comparative Example 3, which lacked clay and water glass, were significantly reduced.

[0032] The molded coke of the present invention includes a non-carbonization process molded coke binder, which can effectively reduce the negative impact on the fixed carbon content, allowing the molded coke to accurately adjust the fixed carbon content, sulfur content, ash content and volatile matter through raw material matching, providing reliable technical guarantees for the large-scale application and promotion of non-carbonization process molded coke in industry.

[0033] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A non-carbonization process coke binder, characterized in that: By weight, it includes the following components: Ceramic fiber: 3-12 parts; Tar asphalt: 5-15 parts; Phenolic resin: 3-10 parts; Clay: 10-20 parts; Water glass: 5-15 parts; Curing agent: 5-10 parts; Plasticizer: 1-5 parts; Waterproofing agent: 1-3 parts; Filling material: 10-20 parts.

2. The method for preparing the non-carbonization process type coke binder according to claim 1, characterized in that: The following steps are involved: S1. Pretreatment: Process the ceramic fiber into a specific size for standby use, and then heat the tar pitch to a specific temperature for standby use; S2, preliminary mixing: adding phenolic resin to the tar pitch in step S1, stirring until the phenolic resin and the tar pitch are evenly mixed to obtain a mixture; S3, secondary mixing: slowly adding clay to the mixture in step S2, stirring until the clay is completely wrapped in the mixture in step S2, adding plasticizer, waterproofing agent and curing agent in sequence, stirring, and then slowly adding water glass, stirring until the water glass and the mixture are evenly mixed; S4, three-time mixing: adding the ceramic fiber in step S1 to the mixture in step S3, stirring until the ceramic fiber and the mixture are evenly mixed, then adding the filling material, stirring, and obtaining the molded coke binder.

3. The method for preparing the non-carbonized process coke binder according to claim 2, characterized in that: The processing method in step S1 is a kind of shearing and grinding.

4. The method for preparing the non-carbonized process coke binder according to claim 2, characterized in that: The specific temperature in step S1 is higher than the softening point of the tar pitch.

5. A molded coke comprising the non-carbonization process molded coke binder as claimed in claim 1, characterized in that: The non-carbonized process coke binder accounts for 10-20% of the total mass of the coke.